The effect of applying anti-osteoporosis drugs on the rehabilitation of patients with rotator cuff tears after arthroscopic rotator cuff repair: a meta-analysis - Yue Hao; Junqing Jia; Junjie Wang; Dongsheng Hao (Journal of Orthopaedic Surgery and Research)
Abstract Background This comprehensive meta-analysis aimed to elucidate the effects of anti-osteoporosis (OP) drugs in patients who experienced rotator cuff tears and underwent arthroscopic repair. Methods The PubMed, Embase, Web of Science, and Cochrane Central databases were searched to identify studies that examined the effects of anti-OP drugs among patients with rotator cuff tears who underwent arthroscopic rotator cuff repair. Specifically, studies that evaluated the retear rate and other subjective or objective outcomes were included in the analysis. The databases were searched from inception to January 13, 2025. Results Ultimately, 5 articles were included in this meta-analysis. Compared with the control group, the anti-OP drug group had a lower retear rate, higher American Shoulder and Elbow Surgeon scores and a greater internal rotation angle. The Simple Shoulder Test, University of California, Los Angeles shoulder score, Constant Shoulder score, and forward flexion angle were not markedly different between the two groups. Conclusion Anti-OP drugs markedly promoted bone-to-tendon healing and improved quality of life among patients who underwent arthroscopic rotator cuff repair, especially with respect to activities that involve internal rotation of the shoulder.